Does brief mindfulness intervention increase performance? An exploratory study - Barbry, A.; Carton, A.; Bernier, M.; Ovigneur, H.; Coquart, J. B. (International Journal of Sports Medicine, 2025)
The effects of mindfulness-based interventions combined with a running programme on physical performance need further investigation. Studies often proposed a long mindfulness intervention with a low-intensity physical activity. This study aims to investigate the effects on physical performance of a brief mindfulness intervention with a running programme. Sixty-five trained runners were randomised in brief mindfulness or control groups. Intermittent maximum speed, heart rate variability and ratings of perceived exertion were performed at baseline, at 4 weeks and 8 weeks. Fat mass and physical fitness were assessed at baseline and 8 weeks after. A time*group interaction was detected for cardiorespiratory fitness tests (i.e. intermittent maximum speed and 3-min shuttle run tests). Cardiorespiratory fitness stagnated for the mindfulness group whereas it decreased significantly over time in the control group (p=0.01). No time*group interactions were detected for the other outcomes (p<0.05). Brief mindfulness intervention might potentially mitigate the fatigue-related performance decrements during the preparatory phase. The cardiorespiratory fitness decrease for the control group could be explained by the high training load during this time of the season. The stagnation in the mindfulness group might be illustrated by the development of some psychological skills.